Pendampingan Pelatihan Strategi dan Daya Saing Toko Tradisional menghadapi Maraknya Toko Modern di Bali - Ni Kadek Suryani; Ni Ketut Karwini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
Abstract The purpose of this community service is to provide assistance and guidance regarding the strategies used in running a traditional retail store business in dealing with the rise of modern stores in the last year. This service was carried out at UD SP, which has three grocery store branches in Batubulan Village, Sukawati District, Gianyar Regency, Bali. This service is carried out by looking directly into the field, with data analysis using a qualitative descriptive approach through SWOT analysis. Observations showed that UD. SP has great advantages and opportunities to remain competitive with modern stores. The main strategy that must be implemented is digitizing operations such as payments, recording transactions and inventory, and promoting them through social media, thereby expanding market reach. Maintaining strengths and trying to improve weaknesses and increase existing opportunities. Key words: business strategy, competitiveness, SWOT analysis